A floating versus managed exchange rate regime in a DSGE model of India - Batini, Nicoletta (2010)
We first develop a two-bloc model of an emerging open economy interacting with the rest of the world calibrated using Indian and US data. The model features a financial accelerator and is suitable for examining the effects of financial stress on the real economy. Three variants of the model are highlighted with increasing degrees of financial frictions. The model is used to compare two monetary interest rate regimes: domestic Inflation targeting with a floating exchange rate (FLEX(D)) and a managed exchange rate (MEX). Both rules are characterized as a Taylor-type interest rate rules. MEX involves a nominal exchange rate target in the rule and a constraint on its volatility. We find that the imposition of a low exchange rate volatility is only achieved at a significant welfare loss if the policymaker is restricted to a simple domestic inflation plus exchange rate targeting rule. If on the other hand the policymaker can implement a complex optimal rule then an almost fixed exchange rate can be achieved at a relatively small welfare cost. This finding suggests that future research should examine alternative simple rules that mimic the fully optimal rule more closely.